2020
DOI: 10.3390/toxins12030161
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Remodeling in Chronic Kidney Disease

Abstract: Cardiac remodeling occurs frequently in chronic kidney disease patients and affects quality of life and survival. Current treatment options are highly inadequate. As kidney function declines, numerous metabolic pathways are disturbed. Kidney and heart functions are highly connected by organ crosstalk. Among others, altered volume and pressure status, ischemia, accelerated atherosclerosis and arteriosclerosis, disturbed mineral metabolism, renal anemia, activation of the renin-angiotensin system, uremic toxins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 106 publications
(151 reference statements)
4
67
0
6
Order By: Relevance
“…Furthermore, as in rodents, accelerated senescence was confirmed in ADMSCs isolated from patients with CKD as compared to those from healthy kidney donors by the findings of higher expression of DNA damage markers γH2AX and 53BP1 as well as CDKN2A and higher percentage of SA‐β‐gal‐positive cells resulting in the upregulation in SASP genes. Our observations showing that CKD causes MSCs to undergo cellular senescence are in accordance with the findings that uremic toxin or hyperphosphatemia can induce senescence of vascular smooth muscle cells (Muteliefu et al, 2012; Takemura et al, 2011; Troyano et al, 2015) or myoblasts (Sosa et al, 2018), which have been suggested as potential mechanisms of cardio‐renal cross talk (Hénaut et al, 2018; Kaesler et al, 2020) or sarcopenia associated with CKD (Sosa et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, as in rodents, accelerated senescence was confirmed in ADMSCs isolated from patients with CKD as compared to those from healthy kidney donors by the findings of higher expression of DNA damage markers γH2AX and 53BP1 as well as CDKN2A and higher percentage of SA‐β‐gal‐positive cells resulting in the upregulation in SASP genes. Our observations showing that CKD causes MSCs to undergo cellular senescence are in accordance with the findings that uremic toxin or hyperphosphatemia can induce senescence of vascular smooth muscle cells (Muteliefu et al, 2012; Takemura et al, 2011; Troyano et al, 2015) or myoblasts (Sosa et al, 2018), which have been suggested as potential mechanisms of cardio‐renal cross talk (Hénaut et al, 2018; Kaesler et al, 2020) or sarcopenia associated with CKD (Sosa et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Either the differences in residual gradients are too small to have a meaningful clinical relevance or other factors such as AF or baseline LVMI have a much greater effect on remodeling than these prosthesis parameters. In the present study, AF patients had more often chronic renal failure, which is known to be associated with LV hypertrophy and fibrosis [30]. This might be another factor for the limited reverse remodeling process in those with AF.…”
Section: Discussionmentioning
confidence: 53%
“…The QTpe interval at all leads and QRS duration were shortened after HD. Patients with a longer uremic toxins, and corrects electrolyte imbalance [30,32], and this might shorten the QTpe interval. A recent study reported no differences in QTpe intervals between the SCD and survivor groups among HD patients, similar to our results [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis to explain these ndings is as follows. Chronic kidney disease frequently causes cardiac remodeling with hypertrophy, capillary loss, and brosis [30]. Progression of myocardial brosis could lead to increased dispersion of repolarization and an increased QTpe interval on ECG [31].…”
Section: Comparison With Other Studies: An Explanatory Hypothesismentioning
confidence: 99%